Penggunaan beluntas, vitamin C dan E sebagai antioksidan untuk menurunkan off-odor (25%) daging itik alabio dan Citaheup - . Rukmiasih; Peni S Hardjosworo; Pius Pertumpuan Ketaren; Procula R Matitaputty (Jurnal Ilmu Pertanian Indonesia, 2010)
Meat consumption of Indonesian society is not limited to the beef and chicken. Meat ducks are now starting to become popular and food products that are brilliant prospects. Sources of duck meat usually from male and female ducks dismissed that as a result of low-quality meat. The purpose of this study is looking at providing beluntas, vitamin c and e on the effectiveness of local men ducks. In the present study utilized two strain Cihateup male duck and Alabio male duck, each of which consists of three repeats with four treatment of forages, namely: 1. KO (control), 2. Beluntas commercial feed + 0.5% (KB), 3. Beluntas commercial feed + 0.5% + vitamint c 250 mg/kg (KBC), 4. Beluntas commercial feed+ 0.5% + vitamint e 400 IU/kg/dose (KBE). Design made of CRD. The results showed that the feed treatment (KB, KBC, KBE) has no effect on feed intake, feed conversion, final weight, body weight gain, weight cut, the percentage of carcasses and carcass parts percentage Alabio duck, but duck feed Cihateup treatment (KBE) significant effect on final weight, percentage body weight gain and carcass parts of the chest compared with treatment C, KB and KBC. The use of leaf starch levels beluntas 0.5°/o yield better feed conversion. Wheat leaf beluntas as much as 0.5% + Vitamint E in the diet, is able to maintain good performance with the ducks.